2019
DOI: 10.1002/glia.23738
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol prevents LPS‐induced microglial inflammation by inhibiting ROS/NF‐κB‐dependent signaling and glucose consumption

Abstract: We used mouse microglial cells in culture activated by lipopolysaccharide (LPS, 10 ng/ml) to study the anti‐inflammatory potential of cannabidiol (CBD), the major nonpsychoactive component of cannabis. Under LPS stimulation, CBD (1–10 μM) potently inhibited the release of prototypical proinflammatory cytokines (TNF‐α and IL‐1β) and that of glutamate, a noncytokine mediator of inflammation. The effects of CBD were predominantly receptor‐independent and only marginally blunted by blockade of CB2 receptors. We es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
100
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 66 publications
19
100
1
Order By: Relevance
“…To further confirm the role of the inflammasome in liver inflammation, the authors studied the effect of CBD on an LPS + ATP treated mouse macrophage cell line, confirming with in vivo data that the expressions of NLRP3, ASC, IL-1β, NF-κB, and caspase-1 were lower in CBD-treated cells ( 195 ). Mouse microglial cells treated with LPS to simulate neuroinflammatory conditions exhibited a robust activation of pro-inflammatory cytokine repertoire, and CBD (1–10 μM) was able to suppress the secretion of IL-1β and inhibit the NF-κB signaling pathway ( 196 ). A similar reduction in the secretion of IL-1β by CBD (10 μM) was also reported by another independent report ( 197 ).…”
Section: Cannabinoids Inflammasomes and Human Diseasesmentioning
confidence: 99%
“…To further confirm the role of the inflammasome in liver inflammation, the authors studied the effect of CBD on an LPS + ATP treated mouse macrophage cell line, confirming with in vivo data that the expressions of NLRP3, ASC, IL-1β, NF-κB, and caspase-1 were lower in CBD-treated cells ( 195 ). Mouse microglial cells treated with LPS to simulate neuroinflammatory conditions exhibited a robust activation of pro-inflammatory cytokine repertoire, and CBD (1–10 μM) was able to suppress the secretion of IL-1β and inhibit the NF-κB signaling pathway ( 196 ). A similar reduction in the secretion of IL-1β by CBD (10 μM) was also reported by another independent report ( 197 ).…”
Section: Cannabinoids Inflammasomes and Human Diseasesmentioning
confidence: 99%
“…Similarly, two tetracycline derivatives doxycycline and COL-3 that possess anti-inflammatory properties, efficiently inhibited dyskinesia in L-DOPA-treated parkinsonian rats (Bortolanza et al, 2020). We also found that co-administration of the TRPV-1 ion channel antagonist capsazepine (CPZ) with cannabidiol (CBD), a cannabis derivative with well-reported antiinflammatory properties (Napimoga et al, 2009;Campos et al, 2012;Mori et al, 2017;Sonego et al, 2018;Dos-Santos-Pereira et al, 2020) improves abnormal involuntary movements induced by L-DOPA in a hemiparkinsonian dyskinetic mouse model (Dos-Santos-Pereira et al, 2016;Junior et al, 2020). Coherent with these observations, abnormal involuntary movements were exacerbated by peripheral administration of the bacterial inflammogen lipopolysaccharide (LPS) in preclinical models of dyskinesia (Mulas et al, 2016).…”
Section: Introductionmentioning
confidence: 77%
“…Other dietary supplementations to consider are: (1) lipoic acid has been shown to inhibit pro-inflammatory IL-6 and IL-17 production ( Salinthone et al, 2010 ); (2) omega-3 fatty acids that are anti-inflammatory and reduce kinase excretion. Consume as a supplement or in form of cod liver oil or fatty fish (such as salmon) once or twice per week ( Vasquez, 2016 ); (3) Cannabidiol (CBD) that promotes anti-inflammatory IL-10 secretion ( Joffre et al, 2020 ) while preventing LPS‐induced microglial inflammation ( dos-Santos-Pereira et al, 2020 ); and (4) Green Tea, since epigallocatechin-3-gallate is the most biologically active catechin in green tea. It reduces Th17 cells and increases regulatory T-cells ( Byun et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%